Pengaruh Model Pictorial Riddle Berbantuan Aplikasi Canva Terhadap Minat Belajar dan Penguasaan Konsep IPA Siswa Kelas IV - Faiqah, Fajriyah Nur; Rukmana, Diki (Jurnal PGSD, 2022)
This study aims to determine the effect of the pictorial riddle model assisted by the Canva application on learning motivation and mastery of science concepts in fourth grade students of SDS Budi Murni Cipayung. This research uses One Group Pretest-Posttest Design. The sample in this study were 12 fourth grade students of SDS Budi Murni Cipayung. Data collection techniques used in this study were questionnaires and tests. The results showed that the learning motivation had a value of tcount (7.892) > ttable (2.2010) at a significance level of 0.05 while for mastery of the concept the value of tcount (11.285) > ttable (2.2010) at a significance level of 0.000 <0.05 . This result shows that the application of the pictorial riddle model assisted by the Canva application has a significant effect on learning motivation and mastery of science concepts for fourth grade students at SDS Budi Murni Cipayung.